Activity based costing: A case study of Raiffeisen Bank of Luxembourg - Julie Wing Yan Chow (European Institute for Knowledge & Value Management (EIKV), 2016)
[Thesis Objective] The following thesis gives an overview about the complex topic of activity-based costing (ABC). In order to understand the concept of ABC, it is necessary to define cost allocation as well as the various methods of cost allocation. Furthermore, there will be a description of the benefits and the limitations of ABC and in order to further understand the ABC, an analysis of the differences between the traditional costing system and the ABC system will be included in this assignment. In addition, as the author is working in the Luxembourg banking sector, the Raiffeisen Bank of Luxembourg, the assignment includes a case study of the process of implementation of the ABC in Raiffeisen Bank of Luxembourg for the purpose of assisting the bank's management in their decision-making in order to succeed in today's business environment. The case study doesn't necessarily have to be exhaustive and include all individual components, but it should reflect the relevant elements of Raiffeisen Bank. In other words, the author will chose four major selling points of Raiffeisen Bank, one of each region, that are prone to represent the whole range of agencies of Raiffeisen bank for the establishment of the process of implementation of the ABC in Raiffeisen Bank. Last but not least, the author doesn't intend to suggest new elements and variables that haven't yet been analysed in literature.
Keywords: 650